Hippocampal high frequency oscillations in unilateral and bilateral mesial temporal lobe epilepsy - Řehulka, Pavel; Cimbálník, Jan; Pail, Martin; Chrastina, Jan; Hermanová, Markéta; Brázdil, Milan (Clinical neurophysiology, 2019)
OBJECTIVE: The main aim of this study was to investigate the potential differences in terms of interictal high frequency oscillations (HFOs) between both hippocampi in unilateral (U-MTLE) and bilateral mesial temporal lobe epilepsy (B-MTLE). METHODS: Sixteen patients with MTLE underwent bilateral hippocampal depth electrode implantation as part of epilepsy surgery evaluation. Interictal HFOs were detected automatically. The analyses entail comparisons of the rates and spatial distributions of ripples and fast ripples (FR) in hippocampi and amygdalae, with respect to the eventual finding of hippocampal sclerosis (HS). RESULTS: In U-MTLE, higher ripple and FR rates were found in the hippocampi ipsilateral to the seizure onset than in the contralateral hippocampi. Non-epileptic hippocampi in U-MTLE were distinguished by significantly lower ripple rate than in the remaining analyzed hippocampi. There were not differences between the hippocampi in B-MTLE. In the hippocampi with proven HS, higher FR rates were observed in the ventral than in the dorsal parts. CONCLUSIONS: Non-epileptic hippocampi in U-MTLE demonstrated significantly lower ripple rates than those epileptic in U-MTLE and B-MTLE. SIGNIFICANCE: Low interictal HFO occurrence might be considered as a marker of the non-epileptic hippocampi in MTLE.
Keywords: dospělí; Female; hipokampus; Electrodes, Implanted; Adult; mladý dospělý; Epilepsy, Temporal Lobe; ženské pohlaví; lidé; epilepsie temporálního laloku; Temporal Lobe; retrospektivní studie; spánkový lalok; Male; amygdala; Amygdala; Young Adult; implantované elektrody; Hippocampus; lidé středního věku; mužské pohlaví; elektroencefalografie; Retrospective Studies; Middle Aged; Electroencephalography; Humans